The Relationship Between Ownership and Dividend Policy: Evidence from Tehran Stock Exchange - Filsaraei, Mahdi; Zarei, Alireza (International Journal of Economics and Financial Issues, 2017)
In this study, the relationship of ownership and dividend policy has been investigated. For this purpose, data of 2080 firm-year were used in the period of 2002-2016. In this study, the effect of ownership on dividend policy was estimated as exogenous. For ownership, we used institutional and corporate type. The results were analyzed through software R by using GLM and PGLM. The simple logistic regression and logistic panel model was fitted and Akaike’s criterion was used for comparing the methods. It was observed that the p-value of institutional and corporate investors is less than 0.05, so these two variables have a significant effect on the dividend policy. For the control variables, observations shows that only net income and firm size don’t have a significant effect on dividend policy but other control variables have a significant effect. Keywords: Dividend policy, corporate ownership, institutional ownership. JEL Classifications: G32, G34, G35